Excessively crying infants are more common among children of parents with restless legs syndrome - Pereira Jr,José Carlos (2015)
OBJECTIVE: We have frequently observed that infants presenting with excessive crying and fussing, or colic at night have parents with Restless Legs Syndrome. Our objective was to determine if these infants are more likely to have parents with Restless Legs Syndrome (Willis-Ekbom Disease). METHODS: We interviewed 67 families with infants and children, in search of a history of excessive crying and fussing during their first four months of life. Their parents were investigated for Restless Legs Syndrome. RESULTS: Among the 134 interviewed parents, 39 (29%) had Restless Legs Syndrome. Among the 96 children, 37 (38%) presented excessive crying and fussing. Of these, 28 (76%) had at least one parent with Restless Legs Syndrome. Among the 59 children without excessive crying and fussing only 14 (24%) had at least one parent with Restless Legs Syndrome. The association between events (children of parents with vs. without Restless Legs Syndrome) was measured by the phi coefficient (0.510), indicating a more than trivial association. The estimated association was 75.7 vs. 27.7, Odds Ratio = 10 at 95% confidence interval, 3.82-26.15). CONCLUSION: Children with excessive crying and fussing were more likely to have at least one parent with Restless Legs Syndrome. The present evidence is insufficient to conclude that infantile excessive crying and fussing is equivalent to a a probable diagnosis of parental Restless Legs Syndrome. However, they provide information as well as the necessary motivation to undertake more extensive studies of infants with excessive crying and fussing.